(untitled) (diségno, 2023)
This issue of the journal, edited by Pilar Chías Navarro, Andrea Giordano and Ornella Zerlenga, takes us back to a conceptual aspect of vision, that is, a particular point of view that ‘looks at’ or ‘narrates’ the world of things from above. Indeed, the editors wish to specify in the introduction how, in both literature and drawing, representation actually constitutes the act of storytelling. The point of view is the eye of the narrating subject, who constructs his story through effective and instrumentally useful languages. [read more]